1963
DOI: 10.4319/lo.1963.8.2.0166
|View full text |Cite
|
Sign up to set email alerts
|

Further Measurements of Primary Production Using a Large‐volume Plastic Sphere

Abstract: The experiment described by McAllister, & (II. ( 1961)) in which a phytoplankton bloom was induced to occur in a free-floating 20-ft diameter thin transparent plastic sphere has been repeated. Daily measurements were made of nutrients, particulate matter, and photosynthetic rates with less frequent assays for vitamins and dissolved organic matter. In situ light was recorded by a bolometcr.The experiment was prolonged to 100 days to study phytoplankton decay, most of this period being in the dark. The phytopla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
113
2
6

Year Published

1973
1973
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 368 publications
(134 citation statements)
references
References 19 publications
13
113
2
6
Order By: Relevance
“…BA was converted to carbon content by a 142 conversion factor of 20 fg C/cell (Lee and Fuhrman, 1987) and CBA by a factor of 250 fg 143 C/cell (Kana and Gilbert, 1987). Phytoplankton C content was obtained by converting chl a 144 using a factor of 50 µg C/µg chl a (Antia et al, 1963) …”
Section: Days 128mentioning
confidence: 99%
“…BA was converted to carbon content by a 142 conversion factor of 20 fg C/cell (Lee and Fuhrman, 1987) and CBA by a factor of 250 fg 143 C/cell (Kana and Gilbert, 1987). Phytoplankton C content was obtained by converting chl a 144 using a factor of 50 µg C/µg chl a (Antia et al, 1963) …”
Section: Days 128mentioning
confidence: 99%
“…-7- Standing crop measurements assay the amount of a characteristic material which may be related to microbial biomass. Analyses of such parameters as particulate organic carbon (POC), particulate organic ,nitrogen (PON), protein, DNA, and carbohydrate are often performed in conjuction with photosynthesis measurements (Antia et al, 1963;Strickland et al, 1969) but are rarely used in field studies of bacterial distribution and growth (but see Hobbie et aL., 1972). An underlying assumption in this type of analysis is that only microorganisms are sampled and subsequently trapped on a filter.…”
Section: Determination Of Microbial Numbers and Activitymentioning
confidence: 99%
“…Harvey (1953), Brown and Richardson (1968), Beale and Appleman (1971) and Sheridan (1972) found an inverse proportion between light intensity and chlorophyll a concentrations for algal cells. Steele and Baird (1962), Antia et al (1963), Coombs et al (1967), Eppley (1968), Strickland et al (1969), Hobson and Pariser (1971), Thomas and Dodson (1972) and Peny (1976) showed that deficiency of P, N and Si could lead to a considerable increase in the organic carbon to chlorophyll a ratios. Caperon and Meyer (1972), Eppley and Renger (1974) and Perry (1976) described a negative correlation between specific growth rate and the organic carbon to chlorophyll a ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Parsons & Strickland (1959) 39.6 Antia et al (1963) 25 Eppley (1968) 22.2-47.5 Eppley et al (1971) 60 Eppley et al (1977) 10-90 Antia et al (1963) 23.5-114 Induced bloom; mixture of 6 diatoms and 1 dinoflagellate Coombs et al (1967) 23.5-29.6 Si-deficiency; Navicula pelliculosa phytoplankton Eppley (1968) (22.2-47.5)-No detectable N;natural population, (71.4-125.0) open sea, composition unknown StricMand et al (1969) 34.5-83.3 N limitation; deep tank population of Caclonia niei Hobson & Pariser (1971) 14.7-100.0 NO, deficiency; Thalassiosira fluviatilis Caperon & Meyer (1972) 55.0-500.0 N limitation; chemostat culture of nalassiosira pseudonana Thomas & Dodson (1972) 19.0-61.8 N limitation; chemostat culture of Chaetoceras gracilis Eppley & Renger (1974) N and P limitation; chemostat culture (1976) 28.6-91.4 of 72alassiosira pseudonana chlorophyll a ratios also hold for benthic diatom population~. Therefore, organic carbon to chlorophyll a ratios were determined for intertidal mobile benthic diatom populations.…”
Section: Introductionmentioning
confidence: 99%